Effect of Sarcopenia on Changes in the Physical Function of Older Inpatients - TAKESHITA, Yasufumi; YANAGITA, Hirokazu; MIYAZAKI, Takasuke; YONETOKU, Kazuhiro; YAMASHITA, Kana; SAKASHITA, Yuji; KUWAZURU, Sho; AKASAKI, Yoshihiko; KAJI, Tomokazu; TAKENAKA, Toshihiro (Rigaku ryoho kagaku, 2021)
[Purpose] This study examined the effect of sarcopenia on changes of the Short Physical Performance Battery (SPPB) in older inpatients. [Participants and Methods] This study recruited 17 older inpatients. Sarcopenia was assessed at the time of the first evaluation, and 11 patients were assessed to have sarcopenia. The improvements in SPPB at 3 weeks from the time of the first evaluation were compared between those with and without sarcopenia using repeated measures analysis of variance. [Results] Although there was no interaction effect in the total SPPB score, both groups showed similar improvements in the total SPPB score after 3 weeks. No interaction effect was also observed in sit-to-stand of SPPB, and a similar trend of improvement was observed, but the sarcopenia group showed lower values than the non-sarcopenia group both at the time of first evaluation and after 3 weeks. [Conclusion] Older inpatients with sarcopenia also showed improvement in SPPB, but may still show a decline in sit-to-stand ability.